Implementasi dan Evaluasi SIK Berbasis PRISM: Studi Kasus Puskesmas X Makassar - Mujtahidah, Mujtahidah; Samsiana, Samsiana; Rachman, Irwandi (Wiraraja Medika : Jurnal Kesehatan, 2025)
A reliable Health Information System (SIK) is a key component in supporting the quality of health services, especially at the primary level, where the availability of accurate and timely data is the basis for planning, monitoring, and decision-making. This study aims to evaluate the implementation of SIK at Puskesmas X, Makassar City, using the Performance of Routine Information System Management (PRISM) framework to assess system performance from input, process, and output aspects. The research method used is a case study through semi-structured interviews, observations, and document review. Three informants were selected purposively with the criteria of informants who are directly involved in the management of the Health Information System at Puskesmas X, Makassar City. Data were analyzed thematically to evaluate the implementation of SIK based on the PRISM framework. The results of the study showed that in the input aspect, adequate hardware and internet connection were available, as well as training support from vendors. In terms of processes, the system has been run according to procedures, but there are still obstacles in the form of connectivity disruptions and limitations of reporting features that only present basic reports, so they do not support more in-depth analysis. In the output aspect, the system simplifies the workflow of officers and speeds up reporting, but the use of data for decision-making is not optimal because it is only used to produce routine reports, without further analysis that can support strategic decision-making. This study concludes that the implementation of SIK at Puskesmas X is going quite well where the available hardware and internet connection show adequate performance and reporting speed that meets the set operational standards. However, strengthening internal policies and sustainable system development is needed to be able to meet the needs of health services as a whole. The novelty of this research lies in the comprehensive application of the PRISM framework in the evaluation of SIK in primary health services.